Phenotypic Plasticity Regulates Candida albicans Interactions and Virulence in the Vertebrate Host - Mallick, Emily M.; Bergeron, Audrey C.; Jones, Stephen K.; Newman, Zachary R.; Brothers, Kimberly M.; Creton, Robbert; Wheeler, Robert T.; Bennett, Richard J. (Frontiers in Microbiology, 2016)
Phenotypic diversity is critical to the lifestyles of many microbial species, enabling rapid responses to changes in environmental conditions. In the human fungal pathogen Candida albicans, cells exhibit heritable switching between two phenotypic states, white and opaque, which yield differences in mating, filamentous growth, and interactions with immune cells in vitro. Here, we addressed the in vivo properties of the two cell states in a zebrafish model of infection. Multiple attributes were compared including the stability of phenotypic states, filamentation, virulence, dissemination, and phagocytosis by immune cells, and phenotypes equated across three different host temperatures. We show that both white and opaque cells can establish a lethal systemic infection. The relative virulence of the two cell types is temperature dependent; virulence is similar at 25°C, but at higher temperatures (30 and 33°C) white cells are significantly more virulent than opaque cells. Despite the difference in virulence, fungal burdens and dissemination are similar between cells in the two states. Additionally, both white and opaque cells exhibit robust filamentation during infection, and mutants unable to filament show decreased virulence, establishing that this program is critical for pathogenesis in both cell states. Interactions between C. albicans cells and immune cells were compared both in vitro and in vivo. Macrophages and neutrophils preferentially phagocytosed white cells over opaque cells in vitro, and neutrophils also showed preferential phagocytosis of white cells in vivo. Together, these studies distinguish the properties of white and opaque cells in a vertebrate host, and establish that the two cell types demonstrate both important similarities and key differences during infection.